1988
DOI: 10.2307/3899381
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation Response to the Santa Rita Grazing System

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 2 publications
5
36
0
Order By: Relevance
“…After 7 years of study on the Santa Rita Experimental Range (SRER) in Arizona, Martin (1973) found greater total grass density in small areas that were rested from grazing in two of three summer growing seasons compared to continuously grazed areas. In contrast, after 12 years of study at a larger scale on the SRER, Martin & Severson (1988) found no difference in total grass density between continuously grazed areas and those rested for two of three summers. They proposed that the improvement in vegetation condition (grass density) between the start of the 7-year study in 1962 and the 12-year study in 1972 contributed to the absence of an effect of rest in the growing season.…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…After 7 years of study on the Santa Rita Experimental Range (SRER) in Arizona, Martin (1973) found greater total grass density in small areas that were rested from grazing in two of three summer growing seasons compared to continuously grazed areas. In contrast, after 12 years of study at a larger scale on the SRER, Martin & Severson (1988) found no difference in total grass density between continuously grazed areas and those rested for two of three summers. They proposed that the improvement in vegetation condition (grass density) between the start of the 7-year study in 1962 and the 12-year study in 1972 contributed to the absence of an effect of rest in the growing season.…”
Section: Introductionmentioning
confidence: 56%
“…Grass density increased from about 1)8 m\ 2 in 1962 to 9)3 m\ 2 in 1969 (Martin, 1973). At the beginning of the grazing system study in 1972, density was 20 m\ 2 and 17 m\ 2 at the end of their study in 1984 (Martin & Severson, 1988).…”
Section: Introductionmentioning
confidence: 95%
“…The site was subjected to year-round cattle grazing between 1957 and 2005 with about 0Ð028 animals ha 1 year 1 , the equivalent of ¾50% forage utilization (Martin and Severson, 1988;Ruyle, 2003). In 2006, the pasture in which our experimental site was located received only minimal grazing of 25 cattle for 9 days and was not grazed by cattle in 2007.…”
Section: Site Descriptionmentioning
confidence: 99%
“…As a result, rotational grazing not only increases grass production, but also increases the stocking rate [27]. The grassland can recover if the degree of damage and richness does not exceed its ecological threshold; otherwise, grassland degradation will take place [28,29].…”
Section: Effects Of Different Grazing Systems On Plant Community Charmentioning
confidence: 99%
“…However, Derek W. Bailey proposed that in arid and semi-arid shrub lands, timely adjustments to animal numbers and practices that improve grazing distribution at regional and landscape scales are more likely to be effective in maintaining or improving rangeland health than fencing and rotational grazing [34]. Martin and his colleagues explain that rotational grazing can Land 2018, 7, 10 8 of 10 facilitate grassland recovery when the grassland is unhealthy, but such effects are minimal when the grassland is healthy [27]; Heitschmidt and his team (1987), who chose cows as their target animals in their experiment in Texas, found that the impacts of rotational grazing and continuous grazing on the environment were basically similar, and that the differences are mainly caused by the difference in grazing intensity [5]. In addition, Heitschmidt (1982) also found that different grazing seasons and grazing systems affect vegetation differently [35].…”
Section: Effects Of Different Grazing Systems On Changes In Ndvi Valuementioning
confidence: 99%